427 Defining the Impact of the Fecal Microbiome and Secretome on Multiple System Atrophy and α-Synuclein Aggregation - Michelle K. Bland; Wolfgang Singer; Marina R. S. Walther-António (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Aim 1: We will determine whether temporal changes in the fecal microbiome signature correlate with a clinical multiple system atrophy (MSA) phenotype. Aim 2: We will evaluate whether secretomes cultured from fecal samples from MSA patients enhance intracellular and extracellular α-synuclein (αSyn) aggregation using in vitro functional assays. METHODS/STUDY POPULATION: Aim 1: Gut microbiome profiling will be performed by 16S rRNA gene sequencing, tandem mass spectrometry for expression proteomics, and targeted metabolomics in fecal samples from 30 MSA cases matched to 30 healthy controls, a Parkinson’s disease comparison group, and household controls. Aim 2: Microbial species will be isolated using dilution-to-extinction on MSA fecal samples and then will be cultured to obtain secretomes. To assess the effect of MSA fecal secretomes on αSyn aggregation, culture media from microbial isolates will be used in fluorescence resonance energy transfer (FRET) assays and luciferase reporter assays, both modified to measure αSyn aggregation. Positive tests will undergo expanded metagenomic characterization of the microbes and secretome to identify potential causative agent(s). RESULTS/ANTICIPATED RESULTS: Based on cross-sectional metagenomic studies on MSA, MSA cases are expected to have genus reductions in Blautia and Dorea (acetate production); Paraprevotella (succinic and acetic acid production); and Ruminococcus, Coprococcus, and Faecalibacterium (butyrate production). Increases in genus Bacteroides (clinical pathogen) and Akkermansia (mucin degradation) and pro-inflammatory families Clostridiaceae and Rikenellaceae are also expected. MSA is predicted to be associated with reduced levels of short chain fatty acids and increased lipopolysaccharide. These microbial proteins and metabolites are anticipated to modulate intracellular and extracellular αSyn aggregation in vitro. Microbe isolation and secretome culturing methods are expected to identify additional drivers of αSyn aggregation. DISCUSSION/SIGNIFICANCE: This study’s novel use of longitudinal sampling, household controls, and secretome culturing aim to develop a more comprehensive understanding of the complex interactions between the gut microbiome and MSA. The success of this work offers the potential for new insights into the impact of the gut microbiome and secretome on MSA and αSyn aggregation.